Record‐High Superconductivity in Transition Metal Dichalcogenides Emerged in Compressed 2H‐TaS2. Issue 9 (27th January 2022) - Dong, Qing; Pan, Jie; Li, Shujia; Fang, Yuqiang; Lin, Tao; Liu, Shuang; Liu, Bo; Li, Quanjun; Huang, Fuqiang; Liu, Bingbing
Abstract: Pressure has always been an effective method for uncovering novel phenomena and properties in condensed matter physics. Here, an electrical transport study is carried on 2H‐TaS2 up to ≈208 GPa, and an unexpected superconducting state (SC‐II) emerging around 86.1 GPa with an initial critical temperature ( T c ) of 9.6 K is found. As pressure increases, the T c enhances rapidly and reaches a maximum of 16.4 K at 157.4 GPa, which sets a new record for transition metal dichalcogenides (TMDs). The original superconducting state (SC‐I) is found to be re‐enhanced above 100 GPa after the recession around 10 GPa, and coexists with SC‐II to the highest pressure applied in this work. In situ high‐pressure X‐ray diffraction and Hall effect measurements reveal that the occurrence of SC‐II is accompanied by a structural modification and a concurrent enhancement of hole carrier density. The new high‐ T c superconducting state in 2H‐TaS2 can be attributed to the change of the electronic states near the Fermi surface, owing to pressure‐induced interlayer modulation. It is the first time finding this remarkable superconducting state in TMDs, which not only brings a new broad of perspective on layered materials but also expands the field of pressure‐modified superconductivity. Abstract : A new high‐ T c superconducting state emerges in 2H‐TaS2 under high pressure. The T c enhances rapidly and reaches a maximum of ≈16.4 K at ≈157.4 GPa, which sets a new record for transition metal dichalcogenides (TMDs). It is the first time this remarkable superconducting state has been found in TMDs. The result brings a new broad perspective on layered materials.